EXPERIMENTAL STUDY OF THE ENERGY CONSUMPTION IN THE REFRIGERATION PROCESS OF SMALL CABINETS (Jóvenes en la Ciencia, 2017)
The study develops a comparison of Diffusion Absorption Refrigeration (DAR) System and Vapor Compressor Refrigeration (VCR) System by using digital multi-meter to measure current and thermocouples to have a measurement in the refrigerators. In the Diffusion Absorption Refrigeration System doesn’t have compressor, it is using ammonia/water with natural convection in the system, therefore it can reduce noise. In the Vapor Compression Refrigeration System is using refrigerant R134a, it is used for household refrigerator, but it still affecting environment and global warming. This system had largest cooling capacity of 55W and coefficient of performance is 2.9. In result of two systems, it has different performance of cooling speed, cooling effect, energy consumption and effect of environment. Environmental issue is the most important we are concerning, vary of technologies let ours living have more convenient, but the energy consumption and materials we are using increases greenhouse effect. Therefore, saving energy, using the high-efficiency environmental refrigerant without pollution, convenient, health and safety that must be evaluated in the selection of the technology for application.